Study protocol for a national retrospective review of femoral periprosthetic fracture management. Is there variation in practice?. Issue 1 (15th October 2021) - Nasser, Ahmed A H; Chauhan, Govind; Osman, Khabab; Nandra, Saroop; Nandra, Rajpal; Mahmood, Ansar
Abstract: Introduction: The incidence of femoral periprosthetic fractures (PPFs) in the UK is on the rise. This rising incidence presents a clinical and an economic burden on the national health care services. There is also uncertainty about the most effective treatment modality for femoral PPFs, as well as a lack of evidence for a standardized management approach. We aimed to identify the true incidence and any variation in the management of femoral PPFs nationally. Methods and analysis: This multicentre national collaborative study has been designed by a trainee led research network in collaboration with a well-established university research organization. Data will be collected from participating centres over a period of 10 years (2010–2019). All adults presenting with a femoral PPF will be identified, and the mode of treatment for each fracture subtype will be recorded. Other measures will evaluate patient and treatment variables, objective and subjective outcome measures. Univariate and multivariate regression analyses will be used, as well as the coefficient of determination (R) in an attempt to measure the degree to which the models could explain the variation in management. Ethics and dissemination: This multicentre national project was approved by the local clinical governance department at each participating hospital site. The results of this study will be submitted to international peer reviewed journals and appropriate national and international conferences.